An integrated investigation of biomarkers' response in crabs (Liocarcinus depurator) and benthic indices at a metalliferous waste discharge area in North Evoikos gulf, Greece. Issue 10 (25th November 2016) - Tsangaris, C.; Kaparou, D.; Bordbar, L.; Simboura, N.; Karris, G.
Abstract : This study applied biomarkers and benthic indices at an area in North Evoikos Gulf, Greece, affected by metalliferous slag disposal. Biomarkers of antioxidant defense (catalase, glutathione S-transferase), and neurotoxicity (acetylcholinesterase) were measured in crabs Liocarcinus depurator. Iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), and zinc (Zn) concentrations in sediments and crabs were also measured. High levels of all metals were found in sediments at the disposal area. Metal levels in the crabs were also higher in the disposal area although spatial differences were not as marked as in the sediments. Accordingly, biomarker responses of crabs in the disposal area were also noted suggesting impact on the antioxidant defense of the organisms against oxidative stress. Benthic indices showed disturbance in the disposal area. The combined approach of measuring biomarkers and contaminant levels in the crabs and sediment was complementary to the benthic indices approach providing indications of metal exposure related effects. Our results support the idea that a twofold monitoring approach of assessing both the benthic community structure shifts and the biomarkers and metal accumulation levels may integrate and capture both the structural and the toxicological effects of dumping onto the benthic communities.